Serum uric acid to creatinine ratio and metabolic syndrome in postmenopausal Chinese women. Issue 17 (April 2020) - Tao, Jing; Shen, Xin; Li, Jie; Cha, Erdenbat; Gu, Pei-Pei; Liu, Jun; Zhu, Wei; He, Lin-Long; Li, Guo-Qing; Wang, Zhao
Abstract : Abstract: This study aimed to investigate the association between Serum Uric Acid (UA) to Creatinine (Cr) Ratio (UA/Cr) and metabolic syndrome (MetS) in postmenopausal women. A total of 455 patients with MetS and 457 age- and gender- matched controls were included in the present retrospective study. Serum levels of total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), fasting plasma glucose (FPG), Cr, and UA were measured. We employed logistic regression analysis to investigate the association between serum UA/Cr and MetS in postmenopausal women. Serum UA/Cr levels were significantly higher in patients with MetS than that in control subjects ( P < .05). In the correlation analysis, serum UA/Cr showed a significantly positive correlation with age, hypertension, systolic pressure (SBP), diastolic pressure (DBP), Waist, body mass index (BMI), TG, UA and negative correlation with type 2 diabetes mellitus (T2DM) and Cr ( P all < .001). Moreover, multivariate analysis revealed that serum UA/Cr was still an independent risk factor for MetS (OR = 2.928, 95% CI = 2.385–3.596, P < .001) after adjustments for other confounders. Serum UA/Cr are strongly associated with the risk of MetS in postmenopausal Chinese women.